Population research of genetic polymorphism transferrin and hemoglobin of some breeds of large horned livestock - A. K. Kadiev (Юг России: экология, развитие, 2015)
Hereditary polymorphism of transferrin and hemoglobin of populations of some breeds of large horned livestock is investigated. Distinctions in frequencies of prevalence of different genotypes and frequencies аллелей these genes as in populations of one breed, and different breeds and their conformity with expected frequencies in aspect of their ecological conditionality are considered.